Experience in Assessing Competencies in Self-Regulted Learning in Blended Learning Environments - S. M. Bakhisheva; G. B. Golub; A. M. Kemeshova; Z. G. Mukhtar; J. S. Kazhiakparova (Высшее образование в России, 2024)
The article deals with the issues related to the definition of students’ competenc-es in the field of self-regulated learning and their assessment in a mixed environment in the con-text of Kazakhstani higher education institution. The aim of the study is to develop an approach to the assessment of self-regulated learning competences of students studying in a blended envi-ronment. The descriptors of competences characterising students’ appropriation of ways of activi-ty were formed; assessment tools have been developed in the form of practice-oriented tasks using the assessment methodology developed by the Samara branch of the RANEPA.The experiment was conducted with the participation of 51 students in the 1st year of the educational programme “Pedagogy and Psychology”. The results of the study allowed us to draw the following conclu-sions: students’ internal resources for regulating their own learning are general competences, which include the following aspects of activity: determining the request for information, extract-ing and primary processing (systematisation) of information, processing information, planning the learning process, evaluating the product and results of learning activities, evaluating and planning their own progression; methods and assessment tools are practice-oriented tasks.